2022
DOI: 10.1155/2022/4331899
|View full text |Cite
|
Sign up to set email alerts
|

Some Recent Modifications of Fixed Point Iterative Schemes for Computing Zeros of Nonlinear Equations

Abstract: In computational mathematics, it is a matter of deep concern to recognize which of the given iteration schemes converges quickly with lesser error to the desired solution. Fixed point iterative schemes are constructed to be used for solving equations emerging in many fields of science and engineering. These schemes reformulate a nonlinear equation f s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Many researchers have found that methods can be combined to design modified iterative techniques for solving nonlinear problems in a wide range of fields, including engineering and science. Some of the recent works can be found in [1][2][3][4][5][6][7][8][9][10][11] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have found that methods can be combined to design modified iterative techniques for solving nonlinear problems in a wide range of fields, including engineering and science. Some of the recent works can be found in [1][2][3][4][5][6][7][8][9][10][11] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%